Creative Thinking and its Relationship to Mathematical Intuition of the Fourth Class Students are Scientific - Salman Al-Sarry, Meeaad Jasim (Opción, 2019)
The aim of the study was to find out the relationship between the skills of creative thinking and mathematical intuition among students in the fourth grade. To achieve this goal, the following hypotheses were developed: 1. There were no statistically significant differences at the level of signifi- cance (0.05) between the theoretical average (mean) and the arithmetical average of the grades of the fourth grade students in the creative thinking test. 2. There were no statistically significant differences at the level of signifi- cance (0.05) between the theoretical average (mean) and the arithmetic average of the students of the fourth grade in the mathematical intuition test. 3. There is no statistically significant correlation between (0.05) among the students in the fourth grade in the two tests creative thinking and mathemati- cal intuition. The research community consisted of 243 students in the fourth grade in the preparatory schools of the General Directorate for the Second Karkh Educa- tion in Baghdad for the year 2018-2019. The research sample was chosen in a simple random way and consisted of (61) students of the fourth grade scientific school And 25% of the members of the total society. The statistical bag for the educational and psychological sciences (SPSS) was used in interpreting the results of the research, which reached: 1. Ownership of the fourth grade students of creative thinking skills. 2. Ownership of students of the fourth grade of scientific mathematical intuition.